25 Years of HOW: A Celebration of Language Teaching and Learning - Ana Clara Sánchez-Solarte (Asociación Colombiana de Profesores de Ingles, 2021)
This article overviews the major themes and pedagogical developments that have emerged via the academic endeavors of practitioners and researchers in the last 30 years, while also touching on how my work adheres to these developments. The document starts with a brief historical background on the establishment of HOW as a resource for the academic community. The next part of the article deals with the theoretical tenets that have influenced my published works. One of those perspectives is the post-method pedagogy, which acknowledges the limitations of attempting to determine what the "best" language teaching method is for everyone, and proposes three parameters to guide language teaching and learning. The next perspective is the psychology of language learning, particularly positive psychology, which is a field that adds balance to the study of negative emotions in the classroom and can be the basis for interventions that aim at enhancing the language learning process. The final construct discussed in the article is metacognition, which refers to how language teachers adapt their mental processes and behaviors to the emerging demands of their context. The article concludes highlighting a number of topics that were relevant three decades ago and that will likely keep their relevance in the future: the complexity of education, the dynamic nature of context and meaning, and the examination of the role of context in the L2 teaching/learning processes, to name only three.